Gluten-Free Corn Cookies Incorporated With Stinging Nettle Leaf Flour: Effect on Physical Properties, Storage Stability, and Health Benefits - Mary Nkongho Tanyitiku; Prisca Bessem; Igor Casimir Njombissie Petcheu (International Journal of Food Science)
The consumption of gluten-free corn cookies is becoming very popular among nonceliac and celiac individuals. However, the absence of gluten and other nutrients in corn generally leads to cookies of lower quality in terms of nutritional value, texture, colour, and shelf life. To improve the quality characteristics of corn cookies, this study investigated the effect of incorporating an underutilised herb (Urtica dioica L. leaves) on its nutritional and physical properties. Stinging nettle leaf flour was incorporated at different levels (5%, 10%, 15%, and 20%) and compared with a control (100% corn cookies). The storage stability of the formulated corn cookies was also investigated at room and frozen (−18±2°C) temperature. The incorporation of stinging nettle leaf flour increased (p<0.05) the ash and protein content of corn cookies from 0.32% (control) to 2.56% (20% stinging nettle leaf flour incorporation) and 6.44% (control) to 21.52% (20% stinging nettle leaf flour incorporation), respectively. After in vitro starch digestion, the total phenolic content (TPC) and antioxidant activity (AA) also increased approximately 27 and seven times, respectively, and the estimated glycaemic index (GI) (eGI) decreased (p<0.05) from 48.60% (control) to 33.18% (20% stinging nettle incorporated). Shelf life characteristics (water activity, peroxide value (PV), and microbial count) of formulated corn cookies were within acceptable limits for human consumption upon storage for 6 months. The findings indicated that stinging nettle leaves could serve as a potential food ingredient in gluten-free bakery products, particularly where low GI foods are desirable.